COMICS AND FILM PEDAGOGICAL STRATEGIES - Koleva, R.J (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The subject of this publication is literary education through visualization with the help of cinema and comics. Relevance is determined by the need to iconize and transmit the most highly concentrated information these days. Iconic signs take on a key role in communication processes. Although the verbal sign system is the most widely used in human practice, we cannot consider it to be absolutely universal and exclusive. Because verbal cues are more difficult to encode and decode due to their high degree of abstractness, it is easier to receive information through images.